From Makkah to Bukit Kamang?: the moderate versus radical reforms in West Sumatra (ca.1784-1819) - Zakariya, Hafiz; Salleh, Mohd Afandi (Centre for Promoting Ideas, USA, 2011)
This study provides a narrative account of the moderate and radical Islah (reform) movements in West Sumatra from 1784-1819. Islah movement at the end of the eighteenth century emerged in response to the peculiar problems confronting the society. Tuanku Nan Tua, the most prominent Islamic scholar in Minangkabau spearheaded this movement by calling people back to shariah peacefully. However, some of his students who were discontent with his peaceful method of reform formed a radical movement. In view of the Padri movement’s militancy and adherence to the strict form of Islam, most of popular literature claims that it was influenced by the “Wahhabi” although there is little historical evidence supporting such contestation.